Effect of Influential Data in 3 ω Fixed Factorial Designs (2015)
This paper provides a methodology alternative for the detection of in- fluential observations in factorial design of fixed effects 3 ω -- Our proposal is developed through the approach of the test statistic (Fq), and the characterization of the impact of such observations on the analysis, the sums of squares and the estimators of the model that describes the experimental design